FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI TADAH HUJAN DI DESA KOTABARU KECAMATAN MARTAPURA KABUPATEN OGAN KOMERING ULU TIMUR - Gumay, Ade Cindya; Lastinawati, Endang; Ogari, Putri Ayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to determine the production factors that influence rainfed rice production in Kotabaru Village, Martapura District, OKU Timur Regency. The implementation of this research was carried out in December 2022-February 2023. The research method was carried out using a survey method. The method of determining the sample used is a simple random sampling (simple random sampling). The population in this study were 141 farmers with a sample of 35 farmers. The analytical method used is cobb douglas multiple linear regression. The results showed that the factors that significantly affected rainfed rice production in Kotabaru Village, Martapura District, OKU Timur Regency were land area, labor, and seeds. Meanwhile, fertilizers and pesticides had no significant effect on rainfed rice production in Kotabaru Village, Martapura District, OKU Timur Regency.